Technique for inrush current modelling of power transformers based on core saturation analysis. Issue 10 (21st March 2018) - Moradi, Arash; Madani, Seyed M
Abstract : Energising a power transformer may cause inrush current, which misleads the protection systems. Therefore, the inrush current analysis is important in designing and protecting power transformers. The non‐linear behaviour of transformer core saturation makes this analysis difficult. Thus, several researches try to model the core saturation and inrush current. This study presents a new technique based on core flux analysis to develop an equivalent circuit for power transformer during inrush current. For this purpose, a new λ – i equivalent circuit is proposed for saturated core transformer by transformation of conventional v – i circuit. This λ – i equivalent circuit clearly shows the effect of parameters on transformer saturation and inrush current; and provides a powerful insight into these phenomena. Moreover, new equations are developed which can predict inrush current and core‐flux envelopes. The predicted waveforms can be compared with measured transformer current to detect transformer internal‐fault during inrush current, which is a challenge in transformer protection. This model and the equations are compared with the recorded inrush current waveform of a real transformer, and simulation results. These comparisons verify the efficiency of the model and accuracy of the equations.